The degree of employing blended learning from the perspectives of principals and teachers of Palestinian public schools in the Nablus district - Hashaika, Sherine Adnan; Darwazeh, Afnan Nazeer (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of employment of blended learning in Palestinian public schools in the Nablus district as seen by principals and teachers, as well as the impact of job and gender on the sample's perspectives. In order to achieve the study's objectives, the survey descriptive curriculum was used, and the tool consists of 7 fields with 49 paragraphs. The study community consists of all principals (182) and teachers (2967) who are male and female in public schools in Nablus Directorate. The questionnaire was distributed electronically to a random sample of 504: 82 of them were principals and (422) were teachers of both sexes in Nablus district, and the data were analyzed using the SPSS statistical programme. The results of the study found that the employment of blended learning in public schools in the Nablus district came at an average level for principals, with an average calculation of 3.33 out of 5 points, and a ratio of 66.6%. For teachers, the level also came at an average of (3.16) out of 5 points and a ratio of 63.2%. The results also showed statistically significant differences between teachers and principals in favor for principals, and there were no statistically significant differences attributable to the gender variable. In light of the results , the study recommended that work should be done to improve the performance of school staff by officials of the ministry of education in cooperation with students and their families to improve the employment of blended learning in Palestinian public schools, and the need to ensure that blended learning is employed in public schools, considering the current seven fields of study, all of which have come at an intermediate level. The researchers proposed further studies on the subject of blended learning by addressing other variables such as scientific qualification, years of experience and technological expertise, as well as similar studies on the employment of blended learning in other districts in Palestine other than Nablus.
Keywords: Employment of blended learning; Nablus District Schools; Principals' and Teachers' Perspective